People's Republic of China : Detailed Assessment Report: CPSS Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report ;, 2012)
The assessment report on the observance of China's compliance with the Committee for Payment and Settlement System's core principles for systemically important payment systems is examined. Domestic foreign exchange transactions are mostly executed at the China Foreign Exchange Trade Center. Domestic payments are handled through a diverse variety of payment systems, mainly operated by the People's Bank of China, except for cards and some local clearinghouses. Real-time remittances, bills, and cheque-clearing services are widely available to the financial institutions serving the rural areas.